2018
DOI: 10.1002/hed.24963
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time to simulation and treatment for patients with oropharyngeal cancer receiving definitive radiotherapy in the era of risk stratification using smoking and human papillomavirus status

Abstract: Increasing time before RT for patients with oropharyngeal SCC is associated with nodal progression and increased hazard of distant failure, although not PFS or OS in our population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…The first negative impact of waiting for treatment to begin is the risk that the tumor will increase in size and/or metastasize during this time, making it harder to treat or resulting in it becoming untreatable [ 7 , 8 ]. However, the time for a tumor to grow is only one of the factors that determines prognosis and the absence of a statistically significant association between TTI and the treatment outcome in our study (and many other reports) is thus not surprising [ 10 – 18 ]. Moreover, no obvious methodological differences could be found between these (negative) studies and the positive studies that confirmed the association between TTI and treatment outcomes [ 33 35 ].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The first negative impact of waiting for treatment to begin is the risk that the tumor will increase in size and/or metastasize during this time, making it harder to treat or resulting in it becoming untreatable [ 7 , 8 ]. However, the time for a tumor to grow is only one of the factors that determines prognosis and the absence of a statistically significant association between TTI and the treatment outcome in our study (and many other reports) is thus not surprising [ 10 – 18 ]. Moreover, no obvious methodological differences could be found between these (negative) studies and the positive studies that confirmed the association between TTI and treatment outcomes [ 33 35 ].…”
Section: Discussionsupporting
confidence: 56%
“…In addition, physical findings documented in clinical records and, when available, diagnostic MRIs were used for this purpose and labelled tumor volumes represented a consensus between two experienced radiation oncologists and a radiologist, all dedicated to HNC management. Like many other studies [ 10 – 18 , 33 36 ], the comorbidity burden was not registered in our patients, although it should be taken into account when assessing survival outcomes [ 49 ]. Finally, lags in the pre-biopsy period were not addressed in our study, including patient delay and delays in referral and diagnostics, which may add significantly to the total TTI.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…HPV negative patients had increased TTI in two studies [38,40]. However, four other studies revealed no association between HPV status and delay [37,39,42,43].…”
Section: Oropharynxmentioning
confidence: 95%
“…[ 18 ] Two other reports from the same study described the effect of time to simulation and treatment for patients with oropharyngeal cancer receiving definitive radiotherapy in smokers and non-smokers. [ 19 ] Our search found 8 review articles on the effect of smoking during cancer treatment. While these publications suggest that smoking is a negative factor for cancer treatment, there is a lack of analyses specifically comparing the variables of drug treatment, current or former smoking status, and cancer type.…”
Section: Introductionmentioning
confidence: 99%